Determinan Persepsi Mahasiswa Mengenai Penggelapan Pajak dengan Penerapan Teknologi Informasi sebagai Variabel Moderasi - Latifah, Jihan; Yeni, Fitri; Permata Sari, Putri Intan (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
The aim of this research is to determine the factors that have an impact on students' views regarding tax evasion with the application of information technology as a moderating variable. The sample in this research is accounting students class of 2020 concentrating on taxation at Putra Indonesia University